Neurophobia: causes and methods to reduce it - Jukna, Š.; Mameniškienė, Rūta (Neurologijos seminarai, 2021)
Neurophobia can be defined as a fear of neurosciences and clinical neurology experienced by students, residents, and doctors due to their inability to apply their knowledge of basic sciences to clinical situations. The concept of neurophobia was first mentioned by Ralph Jozefowicz in 1994, but only in 2002 neurophobia was scientifically proven. Since then, research around the world has shown that medical students rate neurology as the most complex discipline, have the lowest level of confidence in their neurological knowledge, and feel the least confident in their competencies when assessing patients with neurological problems. Neurophobia is thought to be caused by: too short a training period, poor study quality, complex neuroanatomy, difficult neurological examination, neurology training by a non-practicing neurologist, and the stigma that neurologists are dissatisfied with their profession. Medical students and doctors find neurology difficult. Understanding the causes of neurophobia and promoting neurophilia would not only increase the willingness of medical students to choose the profession of neurologist, but also improve the care and treatment of patients with neurological diseases.
Keywords: neurophobia; neurophilia